Unraveling the role of mechanical stimulation on smooth muscle cells: A comparative study between 2D and 3D models. Issue 10 (28th March 2016) - Bono, N.; Pezzoli, D.; Levesque, L.; Loy, C.; Candiani, G.; Fiore, G.B.; Mantovani, D.
ABSTRACT: A thorough understanding of cell response to combined culture configuration and mechanical cues is of paramount importance in vascular tissue engineering applications. Herein, we investigated and compared the response of vascular smooth muscle cells (vSMCs) cultured in different culture environments (2D cell monolayers and 3D cellularized collagen‐based gels) in combination with mechanical stimulation (7% uniaxial cyclic strain, 1 Hz) for 2 and 5 days. When cyclic strain was applied, two different responses, in terms of cell orientation and expression of contractile‐phenotype proteins, were observed in 2D and 3D models. Specifically, in 2D configuration, cyclic strain caused ∼50% of cell population to align nearly perpendicular (80–90 degrees) to the strain direction, while not influencing the contractile‐phenotype protein expression, as compared to the 2D static controls. Conversely, the application of uniaxial strain to 3D constructs induced a ∼60% cell alignment almost parallel (0–10 degrees) to the strain direction. Moreover, 3D mechanical stimulation applied for 5 days induced a twofold increase of SM α‐actin level and a 14‐fold increase of calponin expression as compared to 3D static controls. Altogether these findings provide a new insight into the potential to drive cell behavior by modulating the extracellular matrix and the biomechanical environment. Biotechnol. Bioeng. 2016;113: 2254–2263. © 2016 Wiley Periodicals, Inc. Abstract : In this study, Bono and co‐workers have investigated and compared the response of vascular smooth muscle cells cultured either as 2D cell monolayers and embedded onto 3D collagen‐based gels, in combination with mechanical stimulation (7% uniaxial cyclic strain, 1 Hz). The effects of the combined culture conditions on cells behavior were examined and compared in terms of cell alignment and expression of contractile phenotypic markers.